Geographical differences in survival of dogs with non‐Hodgkin lymphoma treated with a CHOP based chemotherapy protocol. (17th April 2017) - Wilson‐Robles, H.; Budke, C. M.; Miller, T.; Dervisis, N.; Novosad, A.; Wright, Z.; Thamm, D. H.; Vickery, K.; Burgess, K.; Childress, M.; Lori, J.; Saba, C.; et al.
Abstract : Background: In humans geographical differences in the incidence and presentation of various cancers have been reported. However, much of this information has not been collected in veterinary oncology. Aim: The purpose of this study was to determine if a geographic difference in progression free survival exists for dogs with lymphoma treated within the US. Materials and Methods: Medical records of 775 cases of canine lymphoma from 3 US regions (west, south and north), treated with CHOP chemotherapy, were retrospectively evaluated. Cases were collected from referral institutions and were required to have received at least one doxorubicin treatment and have follow up information regarding time to progression. Results: Significant differences in sex ( p = 0.05), weight ( p = 0.049), stage ( p < 0.001), immunophenotype ( p = <0.001), and number of doxorubicin doses ( p = 0.001) were seen between regions. Upon univariate analysis, progression free survival (PFS) differed by region ( p = 0.006), stage ( p = 0.009), sub‐stage ( p = 0.0005), and immunophenotype ( p = 0.001). A multivariable Cox regression model showed that dogs in the western region had a significantly shorter PFS when compared to the south and east. Conclusion: PFS was significantly affected by stage, sub‐stage and phenotype.